A survey of the educational facilities in public and private institutions for child care in the City of Manila and suburbs (1955-1956) - Tan, Alicia J. 1926- ([Quezon City University of the Philippines], 1956)
This study presents comprehensive information and data about the educational facilities in public and private child-caring institutions in the city of Manila and the suburbs. This also includes the types of curriculum offered in institutional schools, the school administration, and the provision and maintenance of the school plants.
Bbliography: l. 170-174.
Thesis (M.Ed.)--University of the Philippines, 1956
Typewritten
Vita
Keywords: Education of children; Education -- Manila